THE ROLE OF INTERACTIVE METHODS IN DEVELOPING STUDENTS’ ENGLISH SPEAKING SKILLS - Ilhomjonova Gulhayo Rustamjonovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This article examines the role of interactive teaching methods in developing students’ English speaking skills. It analyzes how communicative activities such as role-play, group discussions, debates, and problem-solving tasks contribute to improving learners’ fluency, accuracy, and confidence in spoken English. The study highlights that interactive methods create a student-centered learning environment where learners actively participate in real-life communication situations. In addition, the article discusses the effectiveness of modern digital tools and online platforms in enhancing speaking practice. The findings suggest that the use of interactive methods significantly improves students’ motivation and communicative competence in English language learning.